2008
DOI: 10.1080/00365540701805446
|View full text |Cite
|
Sign up to set email alerts
|

Red fox and tick-borne encephalitis (TBE) in humans: Can predators influence public health?

Abstract: Analysing datasets from hunting statistics and human cases of tick-borne encephalitis (TBE), we found a positive correlation between the number of human TBE cases and the number of red fox (Vulpes vulpes). Time lags were also present, indicating that high numbers of red fox in 1 y translated into high numbers of human TBE cases the following y. Results for smaller predators were mixed and inconsistent. Hares and grouse showed negative correlations with human TBE cases, suggesting that they might function as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
16
1
1
Order By: Relevance
“…The negative relationship found in this study between red fox hunting bags and human TBE cases in the succeeding year is in contrast to a study in TBE endemic areas in Sweden, where this relationship was found to be positive [27]. These contradictory findings will need to be clarified in future studies on the specific role of foxes in the epidemiology of TBEV.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…The negative relationship found in this study between red fox hunting bags and human TBE cases in the succeeding year is in contrast to a study in TBE endemic areas in Sweden, where this relationship was found to be positive [27]. These contradictory findings will need to be clarified in future studies on the specific role of foxes in the epidemiology of TBEV.…”
Section: Discussioncontrasting
confidence: 92%
“…Since estimates of wildlife population densities do not exist at the appropriate temporal and spatial resolution, we used hunting bag statistics as proxy for density. We also used hunting bag data of red fox ( Vulpes vulpes ), which was found to be positively correlated (with a time lag of one year) with TBE incidence in humans in Sweden [27]. The explanatory variables investigated in this paper include hunting bag data for red deer, roe deer and red fox, land cover, spring warming increase, and an index of forest fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Possible examples include top predators such as the wolf (Canis lupus) and European lynx (Lynx lynx), which suppress numbers of red fox (Vulpes vulpes) [16], a species positively correlated with tick-borne encephalitis (TBE) in humans [17].…”
Section: Roles Of Wildlife In Tick-borne Diseasesmentioning
confidence: 99%
“…Like the mustelids, mammals in the Procyonidae, Sciuridae and Canidae are also common on farms and in urban areas (Zeiner et al ., 1990; Cleary & Craven, 2005; Haemig et al ., 2008). Originally, the idea of raccoons ( Procyon lotor ) and 13‐lined ground squirrels ( Spermophilus tridecemlineatus ) as potential transmitters of AI viruses was evaluated in experimental infections which resulted in AI positive trachea aspirates from 13‐lined ground squirrels for up to 9 dpi and the seroconversion of a single raccoon (Bailey, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…A concurrent serological survey reported evidence of LPAI infection in raccoons trapped in three US states: Wyoming, Colorado and Maryland (Hall et al ., 2008a). Red foxes ( Vulpes vulpes ) frequent rural and urban habitats (Reperant et al ., 2008) and their proximity to humans has recently been identified as a potential risk factor for tick‐borne encephalitis outbreaks in humans (Haemig et al ., 2008). Their proximity to humans has recently been identified as a potential risk factor for tick‐borne encephalitis outbreaks in humans (Haemig et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%